Picardi, M. S., Tedesco, L.F., y Settimi, S.M., Historia de las políticas públicas agropecuarias. De Hipólito Yrigoyen a Cristina Fernández de Kirchner - Audino, Patricia (Estudios económicos, 2012)
Picardi, M. S., Tedesco, L.F., y Settimi, S.M., Historia de las políticas públicas agropecuarias. De Hipólito Yrigoyen a Cristina Fernández de Kirchner